Измерение характеристик канала распространения для оценки его защищённости в системе MIMO - Кузнецов, А. А.; Домнышев, А. П. (ХНУРЭ, 2012)
Threats of information safety in wireless systems of departmental communication, basically are connected with occurrence in them of channels of outflow. With the help of the wiretap channel the malefactor can somehow intrefere with a link. With the advent of MIMO technology new ways of protection of the information to wireless systems have opened. In order to improve the secrstiveness one has to compute it. The way of measuring channel characteristics for computing secretiveness is described in paper.